(untitled) (Journal of Medicine, 2008)
More than 90 percent of cases of kala-azar in the world occur in India, Bangladesh, Nepal, Sudan, and Brazil. Nearly 25 compounds are reported to have anti-leishmanial effects but not all are in use. The pentavalent antimony compounds have remained as mainstay of treatment for nearly 75 years. However, emergence of resistance led to the use of other compounds like amphotericin B, pentamidine, paromomycin, miltefosine etc. Miltefosine is the only oral agent available and recently has been recommended in the National guideline of Bangladesh. But it has a long half-life of 154 hour and this could encourage development of clinical resistance. Further, rapid therapeutic response along with unsupervised treatment can severely affect compliance, and bring a premature end to this very important arsenal against leishmania. Stimaquine is other oral agent coming in near future along with some promising immunotherapeutic agents and of course the possibility of a vaccine. We can assume that in future, combination of drug will be the desirable solution to combat Kala-azar. Â DOI = 10.3329/jom.v9i2.1438 J MEDICINE 2008; 9 : 90-95